The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/aenm.202200961
|View full text |Cite
|
Sign up to set email alerts
|

Laminated Monolithic Perovskite/Silicon Tandem Photovoltaics

Abstract: Perovskite/silicon tandem photovoltaics have attracted enormous attention in science and technology over recent years. In order to improve the performance and stability of the technology, new materials and processes need to be investigated. However, the established sequential layer deposition methods severely limit the choice of materials and accessible device architectures. In response, a novel lamination process that increases the degree of freedom in processing the top perovskite solar cell (PSC) is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 80 publications
(117 reference statements)
0
16
0
Order By: Relevance
“…[19,26,[83][84][85] Combining a sputtered NiO x layer to provide uniform and conformal coverage with solutionprocessed SAMs as a double-layer HTL has demonstrated comparable or even superior PCEs compared to PSCs using standalone solution-processed SAMs processed over planar and micrometer-sized textured substrates. [4,17,27,49,50,[86][87][88] Given that uniform coverage is even more crucial for a textured surface, this combination is expected to be beneficial. Recently, Liu and coworkers have reported on fully textured, production line compatible monolithic perovskite/Si tandem solar cells with ≈29% PCE.…”
Section: Evaporated 2pacz Over Micrometer-sized Texturesmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,26,[83][84][85] Combining a sputtered NiO x layer to provide uniform and conformal coverage with solutionprocessed SAMs as a double-layer HTL has demonstrated comparable or even superior PCEs compared to PSCs using standalone solution-processed SAMs processed over planar and micrometer-sized textured substrates. [4,17,27,49,50,[86][87][88] Given that uniform coverage is even more crucial for a textured surface, this combination is expected to be beneficial. Recently, Liu and coworkers have reported on fully textured, production line compatible monolithic perovskite/Si tandem solar cells with ≈29% PCE.…”
Section: Evaporated 2pacz Over Micrometer-sized Texturesmentioning
confidence: 99%
“…[49] Critically, deposition of SAM-HTLs has thus far been limited to solution-based methods. [8,44,46,[48][49][50][51][52] Development of alternative scalable deposition methods, such as vacuum-based evaporation techniques, is crucial to improve process flexibility. Commercial PV production lines predominantly utilize vacuum-based deposition methods, allowing ready incorporation of vacuum-based methods for large-scale perovskite production.…”
Section: Introductionmentioning
confidence: 99%
“…Considering cleaner methods for energy conversion, photovoltaics become a key component of the relatively new scientific discipline: integrative technologies. Wu et al [54] recently stated that flexible perovskite/c-Si tandem technology with excellent 27.6% conversion efficiency is the most competitive candidate for the next generation mass-produced solar cells integrated on the buildings' exterior while Roger et al [55] suggested technological solutions for commercially viable production of similar material. Simultaneously, flexible photovoltaic materials capable of high-power conversion efficiency in the low light environments become developed for indoor applications [56] while near-infrared dye-sensitized solar cells can satisfy high aesthetic requirements, if required.…”
Section: Perspectivementioning
confidence: 99%
“…However, one of the most dominant challenges in using this method for PSC fabrication is the sensitivity of organicinorganic perovskite films to high temperatures and pressures due to the volatile components and the soft nature of perovskite films. [66][67][68][69] The lamination methods also have been used for stacking different parts of the OPV devices, including polymeric top electrodes using an adhesive, [70][71][72] the photoactive polymer layer, 73,74 or anode and cathode half stacks. 75,76 Likewise, laminated-OPVs employ similar strategies as laminated-PSCs regarding the substrate, equipment, and processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the most dominant challenges in using this method for PSC fabrication is the sensitivity of organic–inorganic perovskite films to high temperatures and pressures due to the volatile components and the soft nature of perovskite films. 66–69…”
Section: Introductionmentioning
confidence: 99%